INFORMATION SEEKING IN OLDER ADULT RURAL CANCER SURVIVORS: UNMET NEEDS AND SEARCH EXPERIENCES. (20th December 2022) - LaValley, Susan; Crabtree-Ide, Christina; Glaser, Kathryn; Haring, Rodney; Mahoney, Martin; Rodriguez, Elisa; Widman, Christy; Bouchard, Elizabeth
Abstract: Cancer survivors over the age of sixty-five have specialized supportive care needs related to maintaining their health and quality of life after treatment. However, cancer survivors living in rural areas may experience barriers like limited digital infrastructure and/or low health literacy when attempting to access necessary informational resources. This project sought to identify older adult rural cancer survivors' domains of unmet informational support and experiences searching for supportive informational resources. Data from a survey administered to cancer survivors (N=292 with complete age data) in rural areas of Western New York (RUCA codes 7-10) were analyzed using descriptive statistics. Variables of interest included Internet access, information-seeking activities, cancer-related topics of interest, and information search experiences. Fifty-four percent of participants in the sample self-identified as over the age of 65. Among older adult cancer survivors, 62% reported using the Internet. The following topics were identified as unmet cancer survivorship information needs: (1) decreasing the risk of cancer recurrence, (2) new symptoms that warrant contacting one's doctor, and (3) medical advances in treatment. Most older adult respondents (70%) were confident in their ability to find needed health information but 40% were concerned about the quality of the information they found and 31% found their search experience frustrating. While rural cancer survivors have access to digital resources and report confidence in their ability to find survivorship information, our findings highlight the need for tailored information on cancer survivorship and interventions to support information appraisal and selecting high quality informational sources.